A STUDY ON CONSTRUCTS OF EXPERIENCE RESULTING IN CUSTOMER LOYALTY TOWARDS RETAIL OUTLETS IN CHENNAI - Kumarasamy, P.; Palani, A. (International Journal of Psychosocial Rehabilitation, 2020)
The concept of customer experience has turned into an important area of study within the marketing discipline. Customer experience could also help in having a better understanding of brands and the benefits that follow it. Customer experience could influence on brand loyalty and this is especially true in the case of a service-centred marketing setup. It is hoped that this article would provide a framework for analysing the customer experience resulting in customer loyalty related to a retail outlet. The objectives of this study are to identify the identify the constructs influencing customer experience with reference to retail outlets in Chennai and to know the influence of customer experience on customer loyalty. The study has revealed that physical response is the most influencing construct followed by affective response, cognitive response and least influencing construct is social response.